PERAN PERMAINAN OUTBOUND CEPAT TANGKAP BOLA DALAM MENGEMBANGKAN KETERAMPILAN KOGNITIF ANAK USIA DINI DI RA TADIKA ADNANI - Sartika Dewi Harahap; Sarah Citrasari; Siti Nurhaliza Lubis; Nur Khofifah; Syarifah Aini (CV. ADIBA AISHA AMIRA, 2024)
Cognitive development in early childhood is an important focus in education, with the fast outbound game of catching the ball recognized as an effective method in supporting children's holistic development. The research method used is qualitative research. This research aims to explore the role of these games in developing the cognitive skills of early childhood at RA Tadika Adnani. With a qualitative approach and case study design, data was collected through observation, interviews and documentation analysis. Results show challenges in child engagement, emotional responses to challenges, lack of social interaction, and constraints in cognitive abilities. Adjustments are needed in the delivery of game rules, a supportive environment, increased involvement, positive emotional responses, and good social interactions. Continuous evaluation and collaboration between teachers and parents are important in supporting children's holistic development.